Synergistic enhancement of performance and emission profiles in a single cylinder CI-engine: A fuzzy-tuned multi-objective whale optimization algorithm for diesel-hydrogen dual fuel augmentation - Shaikh, Azharuddin; Tarafdar, Anirban; Majumder, Pinki; Kumar Bera, Uttam; Deb, Madhujit (Energy conversion and management, 2024)
•Optimized hydrogen-diesel dual fuel for improved engine performance.•Fuzzy-tuned Whale Algorithm reduces emissions significantly.•Enhanced combustion efficiency with dual fuel integration.•Fuzzy logic ensured adaptive and precise control in real-time.•Advanced algorithmic approach for optimal fuel blending. Diesel-powered internal combustion engines struggle to meet emission standards, prompting the need for innovation. One solution is the hydrogen-diesel dual fuel mode, which enhances engine performance and reduces emissions. Hydrogen, a future energy carrier, can be produced from renewable resources and used in existing diesel engines with minimal modifications. Its higher calorific value, flame speed, and air diffusivity improve engine efficiency and reduce emissions. A hydrogen-diesel dual-fuel system was tested on a single-cylinder, 4-stroke diesel engine to achieve low-carbon, high-efficiency, and clean combustion. The study evaluated the impact of varying hydrogen injection strategies on engine performance and emissions under different loads. Results showed an 11.07 % increase in BTHE at 80 % load under the DH3 injection strategy compared to conventional diesel and a 2.2 % increase in volumetric efficiency at 60 % load. NOx emissions peaked at 10.33 g/kW-hr, while HC emissions dropped to 2.20 g/kW-hr at full load, and soot emissions decreased to 0.29 g/kW-hr at 80 % load. A novel fuzzy-tuned whale optimization algorithm (FTMOWOA) was introduced to optimize engine load and hydrogen injection strategies, achieving the best balance of performance and emission reduction. Under the DH4 injection strategy at 70 % load, the algorithm achieved a BTHE of 30.9 %, volumetric efficiency of 70.47 %, NOx emission of 5.82 g/kW-hr, HC emission of 4.34 g/kW-hr, and soot emission of 0.34 g/kW-hr, advancing sustainable energy solutions in dual fuel applications.